DUALISME KEBIJAKAN PENYETORAN PENERIMAAN NEGARA SEKTOR HULU MINYAK DAN GAS BUMI - Wibowo, Puji (Politeknik Keuangan Negara STAN, 2017)
Transfer or payment policy of national revenue from upstream oil and gas has been interesting to discuss for years. The main issue of this policy is Indonesian government has recognized two models of transfer in oil and gas revenue for national account, which are direct and indirect transfer to national account. Direct transfer is dedicated for oil revenue from Pertamina in Rupiahs, while indirect transfer allows foreign currency (dollars) payments from other sources.This dual policies result in liquidity issues regarding government’s ability to cover liabilities in upstream oil mandated by Production Sharing Contracts (PSC) and regulation. Another issue has been intensively debated with external auditors is national revenue delayed during earning process. By reviewing current business process based on a number of regulations and interviewing with several middle management officers in the Ministry of Finance, we propose two options to consider. First, direct transfer or one-step transfer is modified by gathering all revenue sources from upstream oil and gas either in Rupiahs or dollars. The second model, indirect transfer or two-step transfer gathering all payments from oil and gas lifting in dollars. By considering fiscal impacts of these two alternative payment models, we conclude that the second model is preferable than the first scheme